Intensive Forest Fire Management on Tirumala Hills - Sudarsanam, G.; Venkatramaiah, V.; Krishnaiah, P. (Indian Forester, 2002)
Fire has been the major cause of degradation ofluxuriant micro-ecosystem of Tirumala forests. Firewood extraction and repeated fire had denuded the forests leading to serious soil degradation. Regeneration was limited due to fire especially of endemic species. Due to rapid discharge of the rain water, the percolation is seriously affected and the water table in the townships around has gone deep. The discharge also causes silting every year of the Kalyani dam constructed to augment the drinking water supply to the township. Intensive fire protection measures have rejuvenated the existing root stock of fire hardy species such as P. santalinus, Anogeissus and Chloroxylon etc. The regeneration from seed of fire sensitive species such as Santalum and Shoreas has also improved. Once heavily degraded areas with only Phoenix and Cymbopogon have been converted in ten years into luxuriant forests of original bearing. The elephant population for which this was a habitat once, now migrate to these forests in summer due to the improvement of the habitat. The success of fire control is measured by the Forest Department in terms of regeneration of fire sensitive species. As could be seen from the foregoing fire prevention and control could be managed by using human resources at the economical costs. Since, the TTD forests are not inhabited by intermittent villages it has deployed manpower from the near by townships and villages for various fire protection operations. The cases of other forests may not be similar to TTD forests. The reserve forests in the State of A.P. including the core areas as well as in the perimeter are inhabited by tribal and other weaker sections. Most of the degradation is attributed to the biotic interference by the people and cattle in these areas. Since, the State Government has a large number of Van a Samarakshana Samithi (VSS) groups this could be an important tool for the prevention of fires, fire monitoring and control. It is hoped that the experience in the forest fire control adopted in the TTD forest could be made use of by the policy makers and conservationists.